Analisis Keretakan pada Sambungan Las antara Pipa ASTM A106 dengan Globe Valve - Amri Abdulah; Apang Djafar Shieddique; Jatira Jatira; Dede Ardi Rajab; Sukarman Sukarman (Jurnal Asiimetrik: Jurnal Ilmiah Rekayasa & Inovasi, 2021)
Crack failure often occurs in piping installations, especially in the welding area which can be caused by excessive stress or corrosion of the material. In this case, the crack failure in the HAZ area will be discussed near the pipe connected to the valve for the heat transfer fluid line. The method used in this paper is the inspection of the attached materials using OES (Optical emission spectroscope), observation of pipe and valve joints and failure analysis. From the results of material inspection, it was found that the pipe used was ASTM A106, then from the microstructure it was seen that the grain dimensions were not homogeneous, it would cause the strength of material heterogeneity, then from visual observation, it could be seen that pipe joints and valve misalignment occurred.